Kitchen Utensils, Altarpieces and Friendly Smiles: Paths to Christianity for Refugees with Muslim Backgrounds - A Practice-Theory Approach - Blumgrund, Ilona (Approaching religion, 2025)
Among the high number of asylum seekers arriving in Europe in 2015, thousands converted from Islam to Christianity. An emerging body of scholarship explores these conversions. This article sheds light on the lived experience of converting to Christianity during the asylum process. The data consists of in-depth interviews with five Christian converts granted refugee status in Finland. The theoretical and methodological starting points of the analysis were lived religion and practice theory. The analysis shows that forced migration, materiality, care, experiences of spiritual beings, doctrinal aspects and religious freedom are all relevant factors in the path to conversion. This contrasts with the asylum officials’ emphasis on individualistic and spiritual motives when assessing the credibility of conversion, as identified by previous research. Based on this research, I argue that the non-doctrinal and doctrinal dimensions of conversion should not and cannot be separated. Doctrinal dimensions should not be considered more genuine when assessing the authenticity of conversion in the asylum process, or vice versa. This is also a theological argument for a holistic understanding of Christianity, where the meaning of being Christian extends beyond adopting doctrinal ideas to include material and non-material aspects of life.